2014
DOI: 10.1101/gad.231969.113
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical motion promotes expression of Prg4 in articular cartilage via multiple CREB-dependent, fluid flow shear stress-induced signaling pathways

Abstract: Lubricin is a secreted proteoglycan encoded by the Prg4 locus that is abundantly expressed by superficial zone articular chondrocytes and has been noted to both be sensitive to mechanical loading and protect against the development of osteoarthritis. In this study, we document that running induces maximal expression of Prg4 in the superficial zone of knee joint articular cartilage in a COX-2-dependent fashion, which correlates with augmented levels of phospho-S133 CREB and increased nuclear localization of CRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 45 publications
4
121
0
Order By: Relevance
“…These results strongly suggest that FSS activates the cAMP-PKA-CREB signaling pathway, which results in upregulation of the expression of PlGF. Activation of the cAMP-PKA-CREB pathway by FSS has been observed in diverse cell types, including chondrocytes, 39 osteocytes, 32 and hematopoietic stem cells. 22 Diaz et al 22 showed that the effects of FSS on hematopoiesis are mediated, in part, by a cascade that involves calcium efflux and stimulation of the PGE2/cAMP/PKA signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These results strongly suggest that FSS activates the cAMP-PKA-CREB signaling pathway, which results in upregulation of the expression of PlGF. Activation of the cAMP-PKA-CREB pathway by FSS has been observed in diverse cell types, including chondrocytes, 39 osteocytes, 32 and hematopoietic stem cells. 22 Diaz et al 22 showed that the effects of FSS on hematopoiesis are mediated, in part, by a cascade that involves calcium efflux and stimulation of the PGE2/cAMP/PKA signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Many different signaling modules can activate PKA, including prostaglandins (e.g., PGE 2 ) through the prostanoid receptor ; inflammatory cytokines through interferon signaling (Liu et al, 2004), calcium flux, purinergic ( Jing et al; accompanying paper); and -adrenergic signaling. Because of recent evidence suggesting that PGE 2 is synthesized in response to shear stress (Cherian et al, 2003;Ogawa et al, 2014), and the proposed role of PGE 2 in embryonic hematopoiesis ), PGE 2 is a candidate upstream of PKA for the exploration of shear stress-mediated signaling (Diaz et al; accompanying paper). Indeed, PGE 2 can up-regulate BMP4 in human CD34 + cord blood cells (Goessling et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of protein kinase A (PKA) and its downstream target cAMP response element-binding protein (CREB) by exogenous shear stress has been observed in diverse cell types, including chondrocytes and osteocytes (Cherian et al, 2003;Ogawa et al, 2014). The classic mechanism of PKA activation involves the binding of a ligand to a G proteincoupled receptor and activation of adenylyl cyclase, which converts ATP into the second messenger cyclic AMP (cAMP).…”
Section: Genomic Binding and Interaction Of Creb In K562 Cellsmentioning
confidence: 99%
“…Lubricin coating was reduced on the articular cartilage surface in meniscectomized sheep [78]. The intensive mechanical loading of knee joint, like running, induce Prg4 expression in the superficial zone of articular cartilage in mice [79]. The maximum Prg4-expressing articular cartilage progenitors occurred in the region of knee joints that experience the highest levels of mechanical loading, and thus lie in the central domains of the condyles [79].…”
Section: Lubricin (Prg4)mentioning
confidence: 99%
“…The intensive mechanical loading of knee joint, like running, induce Prg4 expression in the superficial zone of articular cartilage in mice [79]. The maximum Prg4-expressing articular cartilage progenitors occurred in the region of knee joints that experience the highest levels of mechanical loading, and thus lie in the central domains of the condyles [79]. In the current study, less invasive MMx may have caused more expression of lubricin in lateral articular cartilage of femur and tibia ( Figure 13B1) and in medial articular cartilage of femur only ( Figure 13B2).…”
Section: Lubricin (Prg4)mentioning
confidence: 99%